2009
DOI: 10.1017/s0022215109991083
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in patients with Behçet's disease: an audiological and transient evoked otoacoustic emission study

Abstract: Significantly lower mid-frequency amplitudes were found in Behçet's patients on transient evoked otoacoustic emission testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Multisystem, autoimmune diseases such as Wegener granulomatosis, lupus erythematosus and polyarteritis nodosa have been demonstrated to cause sensorineural hearing loss by affecting the inner ear 4 . Also, there are studies in the literature on hearing abnormalities in autoimmune/ autoinflammatory dermatologic diseases such as vitiligo 5,6 , psoriasis [7][8][9][10] and Behçet's disease 11,12 . Vitiligo is an autoimmune disease characterized by the destruction of melanocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisystem, autoimmune diseases such as Wegener granulomatosis, lupus erythematosus and polyarteritis nodosa have been demonstrated to cause sensorineural hearing loss by affecting the inner ear 4 . Also, there are studies in the literature on hearing abnormalities in autoimmune/ autoinflammatory dermatologic diseases such as vitiligo 5,6 , psoriasis [7][8][9][10] and Behçet's disease 11,12 . Vitiligo is an autoimmune disease characterized by the destruction of melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation caused by macrophages, T lymphocytes and macrophage-like melanocytes was determined to cause damage to the inner ear and result in hearing loss 4 . There are many studies investigating hearing loss in various inflammatory dermatoses such as vitiligo, psoriasis, and Behçet's disease [5][6][7][8][9][10][11][12] . However, there has been only one study investigating the audiologic anomalies in AA patients in the literature 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Soylu et al [26] found significant differences in hearing thresholds at frequencies of 250, 500, 2000 and 4000 Hz in patients with Behçet's disease; Ak et al [25] found a statistically significant difference at 250, 500, 4000, 6000 and 8000 Hz. Aslan et al [27] stated that there was a significant difference between patient and control group at 250, 1000, 2000, 4000 and 8000 Hz. In our study, we observed statistically significant differences in frequencies of 500, 1000, 2000 and 8000 Hz in the left ear, and 500, 1000 and 8000 Hz in the right (p < 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Both syndromes have a higher prevalence in the ancient silk road, and some MEFV mutations may increase susceptibility in BD [11] . Cochlear involvement has been shown to be present by audiological assessment in the course of BD [12,13] . Also, in a retrospective study, cerebral stroke in FMF patients has been shown to have a higher prevalence than in the general population.…”
Section: Discussionmentioning
confidence: 99%